Inovasi Pembelajaran Anak Usia Dini melalui Pemanfaatan Loose Parts - Laela Lutfiana Rachmah; Dessy Farantika; Raras Ayu Prawinda; Devi Candra Nindiya; Maulinda Sanjaya Sulistyani (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to describe and analyze teachers' experiences in practicing loose parts media innovation in early childhood learning and its implications for children’s growth and development. This research uses a descriptive qualitative approach with a phenomenological design. The research subjects were four teacher of Al Muhajirin Kindergarten in Malang City. Data were collected through in-depth interviews, observation, and documentation, then analyzed by collecting, reducing, analysis, and verification. The results showed that the loose parts media innovation implemented by Al Muhajirin Kindergarten teachers includes the selection of loose parts materials, movement, learning materials, and songs or rhythms. The use of loose parts media in learning has an impact on children's development, including fine motor development as seen from coordination and the ability to make simple movements. Children's cognitive development increases through the ability to read and recognize letters and numbers. In terms of fine arts, children are able to coordinate movements with rhythm or songs and be creative with loose parts materials. In addition, children's language development can be seen from the increase in vocabulary and reading ability after seeing the shapes or writings that have been arranged.